Pengembangan Pembelajaran Pendidikan Agama Islam Sejkolah Adiwiyata Dalam Menghadapi Era Revolusi Industri 4.0 : Studi Di SMA Negeri 1 Lamongan - Moh. Irmawan Jauhari (Kuttab : Jurnal Ilmu Pendidikan Islam, 2019)
Issues concerning the environment and the industrial revolution must be considered in the world of education. Educational institutions must not be absent, let alone be ignorant of the trends of the times which are continually changing from time to time. For this reason, schools need to pay attention to the provision of education that can help students not stutter in dealing with environmental issues and the rapid development of information technology. This study aims to find out about 1) How the development of adiwiyata PAI learning in the face of the industrial revolution 4.0 era in SMA Negeri 1 Lamongan, 2) How are the supporting and inhibiting factors in the development of PAI learning in adiwiyata schools in the face of the industrial revolution 4.0 era at SMA Negeri 1 Lamongan , 3) How to overcome the inhibiting factors of PAI adiwiyata school learning development in the face of the industrial revolution 4.0 era in SMA Negeri 1 Lamongan, research using this qualitative method successfully concluded, among others: 1) learning conditions, including learning objectives, characteristics of the field of study, constraints learning, student characteristics. 2) Learning methods, including organizing strategies, delivery strategies, management strategies. 3) PAI learning outcomes, including effectiveness, efficiency, learning attractiveness. Supporting and inhibiting factors encountered in the development of PAI learning in the era of the industrial revolution 4.0 is from the educational background of students, extracurricular activities, habituation of school religious programs, infrastructure, student interest, family, and relationships. And how to overcome these inhibiting factors is to provide guidance and direction, provide motivation, and collaborate between students, teachers, and parents.